Determinants of Foreign Exchange Reserves in the BRICS Nations - Romi Suradi; Abigail Meriah Karina Tarigan (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2025)
This research aims to investigate the extent to which remittances, exports, and foreign direct investment influence the foreign exchange reserves in BRICS countries. This study is quantitative in nature, employing a causality approach. The research objects are the BRICS countries, consisting of Brazil, Russia, India, China, and South Africa. The type of data used is secondary data obtained from the World Bank and analyzed using panel data processing techniques. This study uses panel data analysis methods with the help of the EViews program for the period from 2009 to 2023. Kata kunci: Exports, Foreign Exchange Reserves, FDI, Remittances